Experimental study on the influence of different carburized layer depth on gear contact fatigue strength. (January 2020) - Li, Wei; Deng, Shuang; Liu, Bingshu
Highlight: An optimized installation method for staggered tooth meshing test is proposed and verified by finite element simulation. The contact fatigue limit stress value of 20CrMnMo carburized gear under different reliability is obtained. The influence of 20CrMnMo gears with different carburized layer depth on contact fatigue was obtained. Abstract: Contact fatigue is one of the main failure modes of gears. Gear contact fatigue reliability test is not only an important way to understand the gear capacity, but also the data foundation in product design. In this paper, the installation method of gear meshing staggered is used, and the two states of full tooth and staggered meshing are compared and analyzed by simulation software to verify the feasibility of the experimental design proposed in this paper. The gear contact fatigue test method combined with the up-down method and the grouping method is used to obtain test data with a minimum of sample gears. Under a certain degree of confidence interval, the logarithmic normal distribution is used to fit the C-R-S-N curve, and the fatigue limit stress of 20CrMnMo carburized gear under different reliability is obtained. The 20CrMnMo different carburized layer depth gears were tested. The results show that the carburized layer is not as thick as possible and has an optimum value. Too thick a layer depth usually causes deterioration of the surface layer structure or a decrease in residual stress, resulting in a decrease in contact fatigue limit. This provides basic test data for the finite life design and high reliability design of gear contact fatigue.